Efficient S-Acylation of Thiourea - Jones, David J.; Khandavilli, Uday B. Rao; O’Leary, Eileen M.; Lawrence, Simon E.; O’Sullivan, Timothy P. (SynOpen, 2018)
Efficient S-acylation of thiourea using a variety of acid chlorides is reported. Structurally diverse aryl and alkyl substrates are compatible with this methodology. Confirmation that acylation occurs exclusively on the sulfur atom of thiourea is provided by single-crystal X-ray crystallographic analysis.
Keywords: isothiourea; thiourea; organosulfur; sulfur transfer